Jovens que re-criam, sentidos que insurgem: investigando modos de subjetivação no currículo de uma feira de ciências do ensino médio. - Gabriel Nascimento da Silva Santos (2019)
In this research, I aimed to investigate the production of subjectivities on a Science fair curriculum, with high school young students. Thus, I followed the trajectories young people, in their participation process on a national Science fair, which takes place every year at São Paulo Polytechnic School (PoliUSP). With the references of post-critical perspective for educational researches, I came up with an investigation problem: how does a science fair curriculum, with high school Young students, act on youth subjectivities production? I proceeded, then, with the investigation of a national Science fair, comprehending it as a curriculum and adopting methodological resources, with specific selection criteria. I adopted, thus, the strategy of bricolagem for the production of an investigation methodology. Through this methodology I‟ve operated with a composition among some resources: discourse analysis (with inspiration in Michel Foucault) + participatory observation + narrative interviews. I searched, then, through a descriptive analysis, to explain the emergency process of this curriculum – since its disclosure on cyberspace, until the projects presentation, during the days of the event. The specific goals placed for this investigation were: 1 – to map and analyze the genealogical traces that point out the emergency of the Science fair curriculum; 2 – to describe and analyze in which way, on the curriculum, sayings and certain powerknowledge strategies were operating on the demand for subjectivities. Regarding the operational concepts, I proceeded with the selection of what I named as “conceptual lenses”. Through these lenses I observed the analyzed object, with the production of an aestheticanalytical tool, which I named – inspired by Manoel de Barros‟ poetry –de fontanoscópio. This artifact, also created with the possibilities of bricolagem resource, has helped me on the description and the use of the theoretical area in which this studies is involved. This exercise made possible, therefore, the creation of a kind of fontana view, or even a fontanoscopic view on the science fair curriculum, supporting the discussion of the main categories that I chose for the development of this dissertation, such as: curriculum, power-knowledge-re-existence, discourse and subjectivation modes. Thus, the argument which I develop in this research is that there is, on the science fair curriculum, the emergency of a pedagogical incentive technology, which operates through techniques of enchantment, convocation and teaching. This technology demands, therefore, the subject position of Young scientist-researcher, and also the production of research Project with the adoption of experimental-scientific method.